Inovasi Tanam Jagung Double Row Dalam Meningkatkan Produksi Jagung - Muhammad Thamrin; Dafni Mawar Tarigan; Desi Ardilla (JURNAL PRODIKMAS Hasil Pengabdian Kepada Masyarakat, 2018)
PKM was conducted in Desa Namo Mirik, Kecamatan Kutalimbaru, Kabupaten Deli Serdang with partners consisting of 2 farmer groups, Ula Kisat Farmers Group and Sumber Jaya Group. The aim of the PKM program is to establish/develop a group of economically independent communities; help create peace, and comfort in community life; and improve thinking skills and other skills needed (softskill and hardskill). The method used to achieve the objectives of this PKM is to carry out counseling or socialization about corn planting using the double row method. The expected target is a partner capable of carrying out corn planting. The planned activities to be carried out are planting corn with a double row method with a plot of 5 rante or 0.2 Ha. The production results obtained in this activity are corn cobs at 8150 Kg / Ha and corn pipil 6025 Kg / Ha.